Self-aligning prosthetic device for older patients with vascular-related amputations: protocol for a randomised feasibility study (the STEPFORWARD study) - Elizabeth Coleman; Catriona McDaid; Natasha Mitchell; Judith Watson; Kerry Bell; Cleveland Barnett; Martin Twiste; Fergus Jepson; Abayomi Salawu; Dennis Harrison; Natalie Vanicek (BMJ Open)
Introduction The majority of older patients with a transtibial amputation are prescribed a standard (more rigid, not self-aligning) prosthesis. These are mostly suitable for level walking, and cannot adjust to different sloped surfaces. This makes walking more difficult and less energy efficient, possibly leading to longer term disuse. A Cochrane Review concluded that there was insufficient evidence to recommend any individual type of prosthetic ankle-foot mechanism. This trial will establish the feasibility of conducting a large-scale trial to assess the effectiveness and cost-effectiveness of a self-aligning prosthesis for older patients with vascular-related amputations and other health issues compared with a standard prosthesis.Methods and analysis This feasibility trial is a pragmatic, parallel group, randomised controlled trial (RCT) comparing standard treatment with a more rigid prosthesis versus a self-aligning prosthesis. The target sample size is 90 patients, who are aged 50 years and over, and have a transtibial amputation, where amputation aetiology is mostly vascular-related or non-traumatic. Feasibility will be measured by consent and retention rates, a plausible future sample size over a 24-month recruitment period and completeness of outcome measures. Qualitative interviews will be carried out with trial participants to explore issues around study processes and acceptability of the intervention. Focus groups with staff at prosthetics centres will explore barriers to successful delivery of the trial. Findings from the qualitative work will be integrated with the feasibility trial outcomes in order to inform the design of a full-scale RCT.Ethics and dissemination Ethical approval was granted by Yorkshire and the Humber—Leeds West Research Ethics Committee on 4 May 2018. The findings will be disseminated via peer-reviewed research publications, articles in relevant newsletters, presentations at relevant conferences and the patient advisory group.Trial registration number ISRCTN15043643.